2004
DOI: 10.1097/00000478-200404000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Primary Mucinous (So-called Colloid) Carcinomas of the Lung

Abstract: Herein we describe the clinicopathologic and immunohistochemical features of 13 primary mucinous (colloid) carcinomas (MCs) of the lung, an uncommon and controversial tumor. The patients, 7 males and 6 females, ranged in age from 50 to 79 years (mean, 64.5 years). All the tumors presented as a peripheral solitary nodule with gelatinous cut-surface and well circumscribed but lacking a complete fibrous wall. The size ranged from 1 to 5.5 cm. Microscopically, they consisted of neoplastic elements floating in larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(42 citation statements)
references
References 45 publications
4
34
0
Order By: Relevance
“…The mucin pools contain clusters of mucin-secreting tumor cells, which may comprise only a small percentage of the total tumor and, thus, be inconspicuous (Figure 8 A ). 155,156 The tumor cells may consist of goblet cells or other mucin secreting cells. Colloid adenocarcinoma is found more often as a mixture with other adenocarcinoma histologic subtypes rather than as a pure pattern.…”
Section: Pathologic Classificationmentioning
confidence: 99%
“…The mucin pools contain clusters of mucin-secreting tumor cells, which may comprise only a small percentage of the total tumor and, thus, be inconspicuous (Figure 8 A ). 155,156 The tumor cells may consist of goblet cells or other mucin secreting cells. Colloid adenocarcinoma is found more often as a mixture with other adenocarcinoma histologic subtypes rather than as a pure pattern.…”
Section: Pathologic Classificationmentioning
confidence: 99%
“…summarized the imaging manifestations of 18 cases of colloid adenocarcinoma, and concluded that the most common imaging manifestation was ill-defined solid peripheral nodules (eight cases) [2]. Other manifestations included consolidation accompanied by air bronchograms and ground-glass opacities (six cases and four cases, respectively) [2]. A study conducted by Sawada et al .…”
Section: Discussionmentioning
confidence: 99%
“…Colloid adenocarcinoma accounts for 0.24% of all lung cancers [2] and has a 5-year survival rate of 51% [3]. Our understanding of colloid adenocarcinoma is insufficient owing to its low incidence in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, immunohistochemical studies show that in PMACB, the predominant molecule is MUC2 [6, 7, 13], which is negative in normal breast tissue. MUC2 and also, other intestinal secretory mucins [8, 9], have been found in other mucinous adenocarcinomas, such as those of the pancreas [22], salivary glands [23], biliary tract, the ampulla of Vater [24], the stomach [25], endometrium [26], lung [27], and ovary [28], among others.…”
Section: Discussionmentioning
confidence: 99%